2019
DOI: 10.1101/765032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long transposon-rich centromeres in an oomycete reveal divergence of centromere features in Stramenopila-Alveolata-Rhizaria lineages

Abstract: 26Centromeres are chromosomal regions that serve as platforms for kinetochore assembly 27 and spindle attachments, ensuring accurate chromosome segregation during cell division. 28Despite functional conservation, centromere DNA sequences are diverse and often repetitive, 29 making them challenging to assemble and identify. Here, we describe centromeres in an 30 oomycete Phytophthora sojae by combining long-read sequencing-based genome assembly and 31 chromatin immunoprecipitation for the centromeric histone CE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 92 publications
3
10
0
Order By: Relevance
“…This feature is also observed in several other fungi, including Neurospora crassa and Fusarium fujikuroi, in which centromeres are enriched for H3K9me2/3 [44,45]. Similar observations have been made in the oomycete Phytophthora sojae [46]. This is in contrast to S. pombe, in which the CENP-A-enriched regions lack heterochromatin, but pericentric regions are enriched for heterochromatin [19,38,39].…”
Section: Native Centromeres But Not Neocentromeres Are Heterochromatic In C Deuterogattiisupporting
confidence: 77%
“…This feature is also observed in several other fungi, including Neurospora crassa and Fusarium fujikuroi, in which centromeres are enriched for H3K9me2/3 [44,45]. Similar observations have been made in the oomycete Phytophthora sojae [46]. This is in contrast to S. pombe, in which the CENP-A-enriched regions lack heterochromatin, but pericentric regions are enriched for heterochromatin [19,38,39].…”
Section: Native Centromeres But Not Neocentromeres Are Heterochromatic In C Deuterogattiisupporting
confidence: 77%
“…Centromeres are often enriched for a variety of different retrotransposons and other repetitive elements (15,16,25,29,30). We similarly observed that centromeres in all Verticillium species are repeat-rich.…”
Section: Verticillium Finally We Demonstrate That Vdltre9 Is a Hallsupporting
confidence: 64%
“…H3K4me2 borders most centromeres in Z. tritici (27), and is associated with centromeres in S. pombe and some animals and plants (64-67). H3K4me2 has not been observed at centromeres in most fungi, including V. dahliae, and in the oomycete P. sojae (30). Changes in heterochromatin in N. crassa leads to altered CenH3 positioning (25), suggesting that heterochromatin is similarly required for centromere maintenance and function in V. dahliae.…”
Section: Verticillium Finally We Demonstrate That Vdltre9 Is a Hallmentioning
confidence: 98%
See 2 more Smart Citations